Sustaining problem-based learning: A mixed-methods exploration of its long-term effects on primary students’ mathematical problem solving - Hana Abdulmajid Alashwal; Areej Issam Barham (Social Sciences and Humanities Open)
This study aimed to investigate the impact of the Problem-Based Learning (PBL) approach on students’ mathematical problem-solving abilities in primary schools in Qatar. A mixed-methods research design was adopted, involving 117 fifth-grade students and 10 mathematics teachers. Quantitative data were collected through a standardized mathematical problem-solving test, while qualitative insights were obtained from semi-structured teacher interviews.A one-way ANOVA was conducted to confirm baseline equivalence among the groups, followed by an Analysis of Covariance (ANCOVA) to assess post-intervention differences while controlling for pre-test scores. The quantitative findings indicated that students exposed to PBL outperformed their peers in traditional instruction, with the highest gains observed among those who experienced PBL over two academic years.Thematic analysis of the interview data supported the quantitative results. Teachers reported improvements in students’ problem-solving performance and highlighted the development of key skills such as perseverance, critical thinking, reasoning, and the use of multiple representations.Overall, the study provides evidence that sustained implementation of PBL can significantly enhance students’ mathematical problem-solving abilities at the primary level.